A kind of aluminum carbonate chewable tablet and preparation method thereof

Through the dry granulation process, magnesium aluminum carbonate, starch and filler are granulated separately, and the tablet is pressed to make a chewable aluminum carbonate tablet, which solves the problems of poor taste, excessive hardness and excessive disintegration time in the prior art, and realizes the problem of poor taste, excessive hardness and excessive disintegration time in the existing technology. Excellent comprehensive characteristics.

CN115737582BActive Publication Date: 2025-02-11CHONGQING PHARSCIN PHARMACEUTICAL CO LTD
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202211629120.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-12-14
Publication Date
2025-02-11
Estimated Expiration
2042-12-14

AI Technical Summary

Technical Problem

The adhesives and fillers used in the preparation process of existing aluminum magnesium carbonate chewable tablets have poor taste, too large hardness, too long disintegration time, making it difficult to achieve excellent comprehensive characteristics.

Method used

The dry granulation process is used to dry granulate magnesium aluminum carbonate and corn starch, mannitol or xylitol respectively to form two parts of particles, and then mix and press the tablet to avoid the use of adhesives and control the hardness and disintegration time limit of the finished product.

Benefits of technology

It achieves a good taste, suitable hardness, short disintegration time limit, faster anti-acid speed and longer anti-acid maintenance time, achieving excellent comprehensive characteristics.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0003999412680000081
    Figure BDA0003999412680000081
  • Figure BDA0003999412680000091
    Figure BDA0003999412680000091
  • Figure BDA0003999412680000101
    Figure BDA0003999412680000101
Patent Text Reader

Abstract

The invention discloses a hydrotalcite chewable tablet and a preparation method thereof, comprising particles A, particles B and magnesium stearate, wherein the particles A contain 50% hydrotalcite and 4% to 8% corn starch; the particles B contain 3% to 7% corn starch and the remainder filler, and are prepared by dry granulation. The chewable tablet has excellent comprehensive properties, excellent taste, shorter disintegration time, faster anti-acid speed, longer anti-acid maintenance time and suitable hardness.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of pharmaceutical preparations, and particularly relates to a hydrotalcite chewable tablet and a preparation method thereof. Background Art

[0002] Aluminum carbonate is a new type of long-acting antacid. Its molecular structure is arranged in a layered lattice and has multiple pharmacological effects. The first is the effect of neutralizing gastric acid: 1g of aluminum carbonate can neutralize 27.1mmol~27.8mmol of hydrochloric acid to generate two insoluble salts, water and carbon dioxide. When the pH is less than 3, the drug begins to neutralize; when the pH is 5, the reaction stops; when the pH is less than 3, the reaction starts again. Therefore, this drug can maintain the pH value of the stomach between 3 and 5, so that 99% of the gastric acid is neutralized and 80% of the pepsin loses its activity. The anti-acid effect of this product has the characteristics of rapid action, mild effect and long-lasting action time. Secondly, this product has adsorption and binding effects: it can directly inhibit the activity of gastric acid protease by adsorbing and binding it, which is beneficial to the repair of the ulcer surface; this drug can also bind bile acid and adsorb hemolytic phosphorylcholine, thereby preventing these substances from damaging and destroying the gastric mucosa. In addition, this product also has a mucosal protective effect: this drug can stimulate the gastric mucosa to increase the synthesis of prostaglandin E2, thereby enhancing the "gastric mucosal barrier" effect. In addition, aluminum carbonate can also promote the release of epidermal growth factor in the gastric mucosa, increase the content of phospholipids in the hydrophobic layer under the mucus, and prevent gastric mucosal damage.

[0003] Clinically, this product is used for gastric ulcer and duodenal ulcer; acute and chronic gastritis and duodenal ampulla inflammation; reflux esophagitis; and for the symptomatic treatment of stomach discomfort related to excessive gastric acid, such as heartburn, acid reflux, abdominal distension, nausea, vomiting and other symptoms.

[0004] Aluminum carbonate is an antacid, and its key quality attribute is antacidity, which is expressed as antacidity. Further quality evaluation can be carried out by in vitro antacid test to evaluate its antacid speed and antacid maintenance time.

[0005] The original formulation of this product on the market is Bayer's aluminum carbonate magnesium chewable tablets, with the trade name Daxi. According to public information, its prescription composition is simple. In addition to the main drug, it only contains corn starch, mannitol, saccharin sodium, magnesium stearate, mint flavor, and banana flavor. Its simple prescription composition is conducive to maintaining a good taste. In addition, as an acid-reducing drug, it also has excellent performance in terms of anti-acid speed and anti-acid maintenance time.

[0006] In 2018, the US FDA issued a guideline for the quality evaluation of chewable tablets, which discussed the particularity of chewable tablets compared to ordinary tablets and reviewed the quality evaluation research of chewable tablets from the aspects of hardness, taste, disintegration time, etc. Regarding hardness, the FDA generally recommends that chewable tablets should have a lower hardness, such as an average hardness of less than 120N.

[0007] For this product, it is relatively easy to meet the acid resistance index specified in the drug standard. However, it is a challenging task to achieve the quality characteristics of the original formulation and have excellent performance in all aspects. Specifically, the excellent comprehensive characteristics of this product should include the following aspects: (1) good taste; (2) short disintegration time; (3) fast acid resistance speed; (4) long acid resistance maintenance time; (5) appropriate hardness.

[0008] There are many prior arts that disclose the formulation composition and preparation method of aluminum carbonate chewable tablets, most of which adopt wet granulation process. Later developed preparation methods include direct tableting and dry granulation, which are summarized as follows:

[0009] (1) Wet granulation process:

[0010] CN200710093165.8 discloses a hydrotalcite preparation and its preparation process. The prescription of this solution contains mannitol, sodium carboxymethyl starch, magnesium stearate, sweet and sweet essence, and the preparation method is to use pre-coagulated starch slurry as a binder, firstly use shear granulation, and then use one-step granulation to make it. This solution adopts a combination of two wet granulation processes, the process is complicated, and because of the use of a binder, it is easy to cause sticking to teeth and astringency.

[0011] CN201610610562.7 discloses a hydrotalcite chewable tablet and its preparation process. The prescription of this solution contains lactose, mannitol, stevioside, pineapple flavor, and magnesium stearate. The process is a wet granulation process, and polyvinyl pyrrolidone K30 aqueous solution is used as a binder. The binder used in this technical solution will bring a bad taste experience.

[0012] CN202210378555.4 discloses a hydrotalcite chewable tablet and a preparation method thereof, wherein the prescription of the solution contains mannitol, corn starch, sodium saccharin, sodium carboxymethyl starch, purified water, powdered mint flavor and magnesium stearate, and the process is wet granulation, using corn starch slurry as a binder. The solution adopts a wet granulation process, and the process is simple, but because it uses starch slurry, it is easy to cause sticking to teeth and astringency, affecting the taste.

[0013] CN202110036123.0 discloses a hydrotalcite chewable tablet and a preparation method thereof. The prescription of the solution includes hydrotalcite, a diluent, a lubricant and a flavoring agent, wherein the hydrotalcite needs to be micronized and the particle size D 90Control 15μm-10μm. This solution adopts the shear wet granulation process and uses purified water as a wetting agent. The finished product prepared by this solution has a faster acid resistance, but because the main drug needs to be micronized, the particle size control range is narrow, which is not easy to carry out industrial mass production. In addition, water is used as a binder and the wet granulation process is adopted, which easily causes the main drug to stick to the teeth and affects the taste.

[0014] 202210713526.9 discloses a magnesium aluminum carbonate chewable tablet and a preparation method thereof. The filler of this technical case includes a mixture of sugar alcohol and inorganic salts, wherein the inorganic salts include aluminum oxide, magnesium oxide, etc. The preparation method of this scheme adopts some special measures, such as the material needs to be moistened with low-temperature pure water vapor or atomized pure water, the mixed material is first tableted, then dried, granulated, and tableted a second time to obtain the finished product. The inorganic salt used in the filler of this scheme is not a commonly used auxiliary material for chewable tablets, which will cause a bad taste; its process requires wetting the material and secondary tableting, which will cause a complicated process and difficult to industrialize large-scale production.

[0015] (2) Direct tableting process:

[0016] CN201811603597.3 discloses a magnesium aluminum carbonate chewable tablet and its preparation process, wherein the prescription of the scheme contains mannitol, pre-coated starch, microcrystalline cellulose, sweetener, aromatic, flavoring agent, and magnesium stearate. The method adopts direct mixing and tableting, which has the characteristics of simple process, low energy consumption, and low production cost. In order to adapt to the direct tableting of materials, this technical scheme needs to use materials with good compressibility, such as microcrystalline cellulose. The addition of such materials is an unfavorable factor for taste.

[0017] CN202011055907.X discloses a formulation process and application of aluminum carbonate magnesium chewable tablets. The technical solution contains xylitol, pre-coated starch, microcrystalline cellulose, cross-linked sodium carboxymethyl cellulose, sweeteners, flavoring agents, magnesium stearate, and silicon dioxide. In order to adapt to direct tableting, the technical solution also uses microcrystalline cellulose with good compressibility, and in order to ensure disintegration, a disintegrant cross-linked sodium carboxymethyl cellulose is added. The addition of these materials will inevitably affect the taste.

[0018] (3) Dry granulation process:

[0019] CN202110195247.3 discloses a magnesium aluminum carbonate chewable tablet and a preparation method thereof. The prescription of this solution contains a diluent, a binder, a lubricant, a glidant, and a flavoring agent, wherein the binder is selected from povidone, hydroxypropyl cellulose, and hydroxypropyl methylcellulose. The preparation method adopts a common dry granulation process. This technical solution has the characteristics of stable quality, simple process, and low energy consumption. In order to be suitable for the dry granulation process, this solution needs to add a binder, and such a prescription design is also a disadvantage for the taste.

[0020] Most of the existing technologies only solve the production or quality problems of the product from one aspect or some aspects. While solving some problems, other problems also arise, and it fails to achieve excellent comprehensive characteristics. For example, when a wet granulation process is used, a binder or a wetting agent is required. After interacting with the raw materials and excipients, on the one hand, it will cause taste problems such as sticking to teeth, astringency, and gritty feeling. On the other hand, it will cause the disintegration time to be prolonged and affect the acid resistance rate; when a direct tableting process is used, in order to improve the compressibility of the product, a filler with good compressibility needs to be added, and in order to ensure disintegration, a disintegrant needs to be used. These materials are not commonly used materials for chewable tablets and are not conducive to the taste; when a dry granulation process is used, in order to ensure the tableting, a binder needs to be added. The addition of these excipients may cause sticking to teeth and is not conducive to the taste.

[0021] In summary, the prior art still has certain defects. The products obtained are difficult to have excellent comprehensive properties. The inventors have conducted in-depth research on various preparation methods of this variety, striving to use fewer types of excipients like the original research products, ensure good taste, and have excellent comprehensive properties in other aspects. As mentioned above, in the prior art solution, when wet granulation is adopted, it is necessary to add a binder or a wetting agent, which will cause a bad taste of the drug after interacting with the main drug excipients; when direct tableting is adopted, the addition of materials with better compressibility will also affect the taste. The inventors have also conducted in-depth research on the dry granulation process. The biggest challenge of this process is that it is difficult to form during tableting and it is easy to cause cracks. As described in CN202110195247.3, a certain proportion of binder needs to be added, and a large pressure needs to be applied to press and form. This technical solution has the following shortcomings: 1. The adhesive property of the added adhesive is not good for the taste, affecting the patient's feeling when chewing; 2. The hardness of the finished product is relatively high, generally above 130N, which does not meet the general property requirements for chewable tablets and is difficult for patients to take; 3. The hardness of the finished product is relatively high, and the disintegration time is significantly longer than that of the original product. Using the dry granulation process to prepare a product with excellent properties in all aspects is a huge challenge for this product.

[0022] After in-depth research by the inventors, based on the dry granulation process, the process prescription of the marketed product and the existing technology were improved, the granules were creatively divided into two parts for granulation, and the proportion of materials in each part of the granules was studied, and finally the present invention was completed. Summary of the invention

[0023] The object of the present invention is to provide a magnesium aluminum carbonate chewable tablet and a preparation method thereof, wherein the magnesium aluminum carbonate chewable tablet does not contain an adhesive and has a good taste; it can be pressed and formed under a relatively low pressure, and the hardness of the finished product meets the general requirements of the FDA for chewable tablets; and the disintegration time is relatively short, which is equivalent to that of the original product. In addition, the product of the present invention has both a relatively fast acid resistance and a relatively long acid resistance maintenance time. By creatively dividing the particles into two parts for granulation, the obtained product has unexpected quality characteristics and solves various technical problems existing in the prior art. The method adopts a dry granulation process, and the magnesium aluminum carbonate chewable tablet obtained has excellent comprehensive characteristics, specifically, including the following aspects: (1) excellent taste; (2) relatively short disintegration time; (3) relatively fast acid resistance; (4) relatively long acid resistance maintenance time; (5) suitable hardness.

[0024] To achieve the purpose of the present invention, the following embodiments are provided.

[0025] In one embodiment, a hydrotalcite chewable tablet of the present invention is characterized in that it comprises particles A and particles B and magnesium stearate, and is prepared by dry granulation and tableting. Calculated by the total weight percentage of the tablet, the particles A contain 50% hydrotalcite, 4% to 8% corn starch and an appropriate amount of flavoring agent, the particles B are composed of 3% to 7% corn starch, and 33.0% to 42.1% filler, and 0.7% to 1.5% magnesium stearate, wherein the drying loss of corn starch is less than 7%.

[0026] Preferably, the chewable tablet of the present invention is composed of particles A, particles B and magnesium stearate, and is prepared by dry granulation and tableting. Calculated by the total weight percentage of the tablet, the particles A are composed of 50% aluminum carbonate magnesium, 4% to 8% corn starch and an appropriate amount of flavoring agent, the particles B are composed of 3% to 7% corn starch and 33.0%-42.1% filler, and the magnesium stearate is 0.7% to 1.5%, wherein the drying loss of corn starch is less than 7%.

[0027] Preferably, in the chewable tablet of the present invention, the flavoring agent includes flavor and sweetener.

[0028] Preferably, in the chewable tablet of the present invention, the flavoring agent is selected from one or more of mint flavor, banana flavor and saccharin sodium, more preferably three.

[0029] Preferably, in the chewable tablet of the present invention, the filler is mannitol, xylitol or a mixture thereof.

[0030] Preferably, in the chewable tablet of the present invention, 90% of the hydrotalcite particles have a diameter less than 150 μm.

[0031] Preferably, in the chewable tablet of the present invention, 90% of the hydrotalcite particles have a diameter of less than 120 μm.

[0032] Preferably, in the chewable tablet of the present invention, 90% of the hydrotalcite particles have a diameter of less than 90 μm.

[0033] In another embodiment, a method for preparing the hydrotalcite chewable tablet of the present invention comprises the following steps:

[0034] 1) mixing hydrotalcite, corn starch and flavoring agent uniformly, and dry granulating to obtain granules A;

[0035] 2) mixing corn starch and filler uniformly, and dry granulating to obtain granules B;

[0036] 3) Mixing the granules A of step 1) and the granules B of step 2) and the magnesium stearate, mixing them evenly, and tableting them to obtain chewable tablets.

[0037] There is no order requirement for steps 1) and 2).

[0038] The hydrotalcite mentioned above refers to hydrotalcite tetrahydrate that meets pharmaceutical requirements, and its molecular formula is Al2Mg6(OH)16CO3·4H2O. 90% of the hydrotalcite particles have a particle size of less than 150 μm; preferably, 90% of the particles have a particle size of less than 120 μm; and more preferably, 90% of the particles have a particle size of less than 90 μm.

[0039] The corn starch mentioned above refers to corn starch that meets the requirements for pharmaceutical use. In order to realize the present invention, it is particularly required that the drying loss of corn starch is less than 7%. The drying loss limit of corn starch in the pharmacopoeia standard is 14%. Controlling this index below 7% can be achieved in a variety of ways, such as drying, or making requirements to the material supplier.

[0040] The filler is selected from mannitol and xylitol; preferably, the filler is selected from mannitol.

[0041] In order to achieve a better taste effect, a flavoring agent can also be added to the prescription. The above-mentioned flavoring agent is selected from flavors and sweeteners. The flavor is selected from mint flavor and banana flavor, and the sweetener is selected from saccharin sodium.

[0042] The positive effects of the present invention are described below in conjunction with the prior art documents:

[0043] The aluminum carbonate magnesium chewable tablets of the present invention contain the same types of auxiliary materials as the original preparation, only corn starch as a disintegrant, mannitol or xylitol as a filler, and magnesium stearate as a lubricant. This technical solution does not contain other auxiliary materials, such as the adhesive polyvinyl pyrrolidone K30 required for wet granulation, the disintegrant sodium carboxymethyl starch; microcrystalline cellulose for direct tablet compression; and the adhesive hydroxypropyl cellulose or hydroxypropyl methylcellulose required for other dry granulation processes. This product needs to be taken after chewing, uses fewer types of auxiliary materials, and mainly uses the common auxiliary materials for chewable tablets, which can ensure the good taste of this product, which is very important for this product. In addition to the main drug, this product uses less starch, and the auxiliary materials used in a larger amount are mannitol or xylitol. Mannitol absorbs heat when dissolved, has a sweet taste, and is comfortable to the oral cavity, and is widely used in the manufacture of chewable tablets. Xylitol is equivalent to sucrose in sweetness, and can produce a significant cool feeling when dissolved. It is very effective in improving the taste of tablets and covering up the bad taste of certain drugs and auxiliary materials, and is also commonly used in chewable tablet production. By using fewer types of excipients, the design can be consistent with the original formulation, giving it a good taste.

[0044] The present invention adopts a dry granulation process to divide the material into two parts for granulation, namely aluminum carbon magnesium and corn starch, and mannitol and corn starch. Studies have found that when the main drug, starch, and mannitol are dry granulated together, it is easy to break during tableting, and the disintegration time of the finished product is longer, which is significantly longer than the original preparation. One way to solve the problem of breaking is to add an adhesive, such as the solution adopted by Chinese patent application CN202110195247.3. The breaking is mainly due to the poor binding force between the materials. The addition of an adhesive is conducive to increasing the bonding between the materials. This is a common means of solving such problems in the field of preparations. However, the finished product obtained in this way still has the following problems: (1) Due to the use of an adhesive, it is easy to cause sticking to the teeth, thereby affecting the taste; (2) It requires a large pressure to press and form, and the hardness of the finished product is relatively large, generally above 130N, which does not meet the current general characteristics requirements for chewable tablets; (3) The large hardness also makes the disintegration time of the finished product longer, which is significantly longer than the original preparation. In view of this problem, the inventors made an in-depth study and surprisingly found that the problem of flakes can be solved by using the decomposition principle to dry granulate the main drug and corn starch, and mannitol and corn starch separately, and then mix the obtained granules and press them into tablets. The sample prepared in this way can be pressed into shape under relatively low pressure, and the average hardness can be controlled below 120N, which meets the requirement that the hardness of chewable tablets generally needs to be less than 120N.

[0045] The inventors have conducted in-depth research on the two-part granulation process, hoping that this method can not only solve the problem of tablet cracking, but also make the finished product have a shorter disintegration time. The results show that the moisture content of starch affects the disintegration time of this product. The pharmacopoeia stipulates that the limit of starch drying loss is 14%. In order to realize the present invention, the moisture content of corn starch needs to be strictly controlled, and the drying loss needs to be controlled to less than 7%. In order to achieve this goal, it can be achieved in a variety of ways, such as drying the starch, or making requirements on material suppliers. For the two kinds of granules of aluminum carbon magnesium and corn starch, mannitol and corn starch, starch is used as a disintegrant, and the material dosage is studied. For aluminum carbon magnesium and corn starch granules, containing 50% aluminum carbonate magnesium, the amount of corn starch is 4% to 8%; for granules composed of mannitol or xylitol and starch, the amount of corn starch is 3% to 7%. Surprisingly, by controlling the moisture content of corn starch and optimizing the dosage, a shorter disintegration time of the finished product is achieved, which is basically equivalent to the original preparation. A shorter disintegration time can achieve a faster acid resistance of this product. The acid resistance study shows that the finished product of the present invention also has a long acid resistance maintenance time.

[0046] In summary, the aluminum carbonate magnesium chewable tablets prepared in the present invention have excellent comprehensive properties, specifically, including the following aspects: (1) excellent taste; (2) shorter disintegration time; (3) faster anti-acid speed; (4) longer anti-acid maintenance time; (5) suitable hardness. DETAILED DESCRIPTION

[0047] The following examples are representative only, for illustrating and helping to understand the spirit of the present invention, but are not intended to limit the scope of the present invention in any way. Any simple modification and adaptation carried out under the spirit of the present invention also belong to the scope of the present invention.

[0048] Example 1 Aluminum carbonate chewable tablets

[0049] Prescription see Table 1

[0050] Table 1 Prescription of Example 1

[0051]

[0052] Preparation method:

[0053] The hydrotalcite chewable tablets are prepared according to the dry granulation process, and the specific process is as follows:

[0054] 1) According to the prescription composition, the raw and auxiliary materials of granules A and B are weighed respectively, wherein the particle size of 90% of the hydrotalcite is controlled to be less than 120 μm, and the drying loss of corn starch is less than 7%.

[0055] 2) Particle A and Particle B were mixed separately in a mixer at a mixing speed of 10 rpm and a mixing time of 10 min.

[0056] 3) The materials mixed in step 2) are granulated into granules respectively by dry granulation process to obtain granules A and B. The process conditions of dry granulation of granules A are: pressing speed 10 rpm to 20 rpm, pressure 10 bar to 20 bar, material gap 1.0 mm to 2.5 mm, granulation speed 100 rpm to 120 rpm, and screen mesh aperture 1.2 mm; the process conditions of dry granulation of granules B are: pressing speed 8 rpm to 15 rpm, pressure 40 bar to 100 bar, material gap 1.0 mm to 2.5 mm, granulation speed 100 rpm to 120 rpm, and screen mesh aperture 1.2 mm.

[0057] 4) Granules A and B prepared in step 3) and the added magnesium stearate were mixed in a mixer at a mixing speed of 10 rpm for 10 min.

[0058] 5) tabletting the mixed material in step 4) to obtain hydrotalcite chewable tablets. During tabletting, the pre-pressure and main pressure are adjusted appropriately to control the friability to be below 1.0% and obtain a finished product with an average hardness of below 115N.

[0059] Example 2 Hydroaluminum carbonate chewable tablets

[0060] Prescription see Table 2

[0061] Table 2 Prescription of Example 2

[0062]

[0063] Preparation method:

[0064] The hydrotalcite chewable tablets are prepared according to the dry granulation process, and the specific process is as follows:

[0065] 1) According to the prescription composition, weigh the raw and auxiliary materials of granules A and B respectively, wherein the particle size of 90% of hydrotalcite is controlled to be less than 150 μm, and the drying loss of corn starch is less than 7%.

[0066] 2) The materials of granule A and granule B were mixed separately in a mixer at a mixing speed of 10 rpm and a mixing time of 10 min.

[0067] 3) The materials mixed in step 2) are granulated into granules respectively by dry granulation process to obtain granules A and B. The process conditions of dry granulation of granules A are: pressing speed 10 rpm to 20 rpm, pressure 10 bar to 20 bar, material gap 1.0 mm to 2.5 mm, granulation speed 100 rpm to 120 rpm, and screen mesh aperture 1.2 mm; the process conditions of dry granulation of granules B are: pressing speed 8 rpm to 15 rpm, pressure 40 bar to 100 bar, material gap 1.0 mm to 2.5 mm, granulation speed 100 rpm to 120 rpm, and screen mesh aperture 1.2 mm.

[0068] 4) Granules A and B prepared in step 3) and the added magnesium stearate were mixed in a mixer at a mixing speed of 10 rpm for 10 min.

[0069] 5) tabletting the mixed material in step 4) to obtain hydrotalcite chewable tablets. During tabletting, the pre-pressure and main pressure are adjusted appropriately to control the friability to be below 1.0% and obtain a finished product with an average hardness of below 115N.

[0070] Example 3 Hydroaluminum carbonate chewable tablets

[0071] Prescription see Table 3

[0072] Table 3 Prescription of Example 3

[0073]

[0074] Preparation method:

[0075] The hydrotalcite chewable tablets are prepared according to the dry granulation process, and the specific process is as follows:

[0076] 1) According to the prescription composition, the raw and auxiliary materials of granules A and B are weighed respectively, wherein 90% of the hydrotalcite particle size is controlled to be less than 90 μm, and the drying loss of corn starch is less than 7%.

[0077] 2) Particle A and Particle B were mixed separately in a mixer at a mixing speed of 10 rpm and a mixing time of 10 min.

[0078] 3) The materials mixed in step 2) are granulated into granules respectively by dry granulation process to obtain granules A and B. The process conditions of dry granulation of granules A are: pressing speed 10 rpm to 20 rpm, pressure 10 bar to 20 bar, material gap 1.0 mm to 2.5 mm, granulation speed 100 rpm to 120 rpm, and screen mesh aperture 1.2 mm; the process conditions of dry granulation of granules B are: pressing speed 8 rpm to 15 rpm, pressure 40 bar to 100 bar, material gap 1.0 mm to 2.5 mm, granulation speed 100 rpm to 120 rpm, and screen mesh aperture 1.2 mm.

[0079] 4) Granules A and B prepared in step 3) and the added magnesium stearate were mixed in a mixer at a mixing speed of 10 rpm for 10 min.

[0080] 5) tabletting the mixed material in step 4) to obtain hydrotalcite chewable tablets. During tabletting, the pre-pressure and main pressure are adjusted appropriately to control the friability to be below 1.0% and obtain a finished product with an average hardness of below 115N.

[0081] Comparative Example 1

[0082] The sample was prepared according to the contents disclosed in Example 1 of Chinese patent application CN202110195247.3. The prescription is shown in Table 4

[0083] Table 4 Prescription of aluminum carbonate chewable tablets of comparative example 1

[0084] Ingredients Prescription ratio Dosage per tablet (mg) Dosage per 1000 tablets (g) Aluminum carbonate 50% 500 500 Mannitol 34.1% 341 341 Sorbitol 10% 100 100 Povidone 4% 40 40 Magnesium Stearate 0.8% 8 8 talcum powder 1% 10 10 Stevioside 0.04% 0.4 0.4 Strawberry flavor 0.06% 0.6 0.6 total 100.00% 1000 1000

[0085] Preparation method: According to the method disclosed in the patent application, dry granulation is adopted, and the steps are as follows:

[0086] 1) Weigh the raw and auxiliary materials according to the mass ratio in the table.

[0087] 2) Premixing: Hydrotalcite API (particle size D 90 The particles are controlled below 180 μm), diluents (mannitol, sorbitol) and adhesives (povidone K30) are placed in a mixer for premixing at a mixing speed of 10 rpm for 5 min.

[0088] 3) Granulation: The mixed powder premixed in step 2) above was used to prepare granules using a dry granulator. The conditions for dry granulation were as follows: screw speed 20 rpm, roller speed 8 rpm, granulation speed 150 rpm, roller pressure 30 bar, and screen aperture 1.0 mm.

[0089] 4) Total mixing: The granules prepared in step 3) are placed in a mixer and mixed with an external glidant (talc), a lubricant (magnesium stearate) and a flavoring agent (stevioside, strawberry flavor) at a mixing speed of 10 rpm for a total mixing time of 5 min.

[0090] 5) Tableting: tabletting is performed using a tablet press to obtain aluminum carbonate chewable tablets.

[0091] Comparative Example 2

[0092] The original preparation of this variety, aluminum carbonate magnesium chewable tablets from Bayer, Germany, with the trade name Daxi, was purchased as Comparative Example 2.

[0093] Performance index detection

[0094] The relevant performance indicators of the samples of Example 1-3 and Comparative Example 1-2 were tested.

[0095] 1. Hardness, disintegration time and acid resistance test

[0096] The hardness of the sample was tested with a hardness tester, the disintegration time was tested according to the pharmacopoeia method, and the antacidity was tested using the determination method under the "Antacidity" item of "Magnesium Aluminum Carbonate Chewable Tablets" of the "Chinese Pharmacopoeia 2020 Edition". The results are shown in Table 5 below.

[0097] Table 5 Hardness, disintegration time and acid resistance test results

[0098]

[0099] It can be seen from the above results that the average hardness and disintegration time of the samples of Example 3 are similar to those of the original preparation, while the two indicators of Comparative Example 1 are quite different from those of the original preparation.

[0100] 2. Taste Evaluation

[0101] 25 volunteers conducted blind tasting evaluations on 5 batches of samples of aluminum carbonate magnesium chewable tablets using the oral tasting scoring method, respectively, from the perspectives of chewing difficulty, mouthfeel after chewing, and comfort after taking. The scoring points and standards are shown in Table 6 below.

[0102] Table 6 Taste rating criteria for aluminum carbonate chewable tablets

[0103]

[0104] The taste evaluation results of 5 batches of samples are shown in Table 7 below (the results are rounded off to one significant figure).

[0105] Table 7 Taste evaluation results of aluminum carbonate chewable tablets

[0106]

[0107] It can be seen from the above results that the taste evaluation of the samples in Example 3 is similar to that of the original preparation and is significantly better than that of the sample in Comparative Example 1.

[0108] 3. In vitro acid resistance evaluation

[0109] The Rossett-Rice in vitro acid-fast test was used to evaluate the acid-fast rate and the acid-fast maintenance time.

[0110] The in vitro acid resistance test method is as follows: add 30ml of water and 70ml of 0.1mol / L hydrochloric acid solution to the reaction vessel, and use a magnetic heating stirrer and a contact thermometer to control the reaction solution at 37℃±0.5℃. Turn on the magnetic stirring at a speed of 400rpm, and use a pH meter to measure the change in pH value in the reaction vessel. Turn on the constant flow pump and pump 0.1mol / L hydrochloric acid solution at a constant temperature of 37℃ into the reaction vessel at a rate of (2.0±0.1)ml / min. After adding the aluminum carbonate magnesium chewable tablets (a dosage of aluminum carbonate magnesium is 1g), immediately turn on the constant flow pump and magnetic stirrer, and record the time and pH value. The results are shown in Table 8.

[0111] Table 8 Hydroaluminium Hydrocarbonate Chewable Tablets In Vitro Acid Resistance Test Results

[0112]

[0113] From the above results, it can be seen that the time to reach pH 3 for samples in Examples 1-3 is comparable to that of the original preparation, and is significantly faster than that of the sample in Comparative Example 1, indicating that in terms of the acid resistance speed, the samples of the present invention can take effect faster; the pH 3-pH 5 retention time for samples in Example 3 is comparable to that of the original preparation, and is significantly longer than that of the sample in Comparative Example 1, indicating that in terms of the acid resistance maintenance time, the samples of the present invention can exert a longer-lasting drug effect.

Claims

1. A hydrotalcite chewable tablet, characterized in that: The chewable tablet is composed of particles A and particles B and magnesium stearate, and is prepared by dry granulation and tableting. In terms of the total weight percentage of the tablet, the particles A are composed of 50% hydrotalcite, 4% to 8% corn starch and an appropriate amount of flavoring agent, the particles B are composed of 3% to 7% corn starch and 33.0% to 42.1% filler, and the magnesium stearate is 0.7% to 1.5%, wherein the corn starch has a drying loss of less than 7%, and the filler is mannitol, xylitol or a mixture thereof, wherein, 90% of the hydrotalcite has a particle size of less than 150 μm.

2. The chewable tablet according to claim 1, wherein the flavoring agent comprises flavor and sweetener.

3. The chewable tablet according to claim 2, wherein the flavoring agent is selected from one or more of mint flavor, banana flavor and saccharin sodium.

4. The hydrotalcite chewable tablet according to claim 1, wherein 90% of the hydrotalcite has a particle size of less than 120 μm.

5. The hydrotalcite chewable tablet according to claim 1, wherein 90% of the hydrotalcite has a particle size of less than 90 μm.

6. A method for preparing the hydrotalcite chewable tablet according to any one of claims 1 to 5, comprising the following steps: 1) mixing hydrotalcite, corn starch and flavoring agent uniformly, and dry granulating to obtain granules A; 2) mixing corn starch and filler uniformly, and dry granulating to obtain granules B; 3) Mixing the granules A of step 1) and the granules B of step 2) and the magnesium stearate, mixing them evenly, and tableting them to obtain chewable tablets. There is no order requirement for steps 1) and 2).

Citation Information

Patent Citations

  • Rapidly effectual aluminum magnesium carbonate preparation and technique of preparing the same

    CN101219150A

  • Hydrotalcite chewable tablet and preparation process thereof

    CN106214647A

  • Hydrotalcite chewable tablet and preparation process thereof

    CN109453131A

  • Formula process and application of hydrotalcite chewable tablets

    CN112220800A

  • Hydrotalcite chewable tablet and preparation method thereof

    CN112675192A